Heart Rate Dependency of Large Artery Stiffness. Issue 1 (July 2016) - Tan, Isabella; Spronck, Bart; Kiat, Hosen; Barin, Edward; Reesink, Koen D.; Delhaas, Tammo; Avolio, Alberto P.; Butlin, Mark
Abstract : Carotid-femoral pulse wave velocity (cfPWV) quantifies large artery stiffness, it is used in hemodynamic research and is considered a useful cardiovascular clinical marker. cfPWV is blood pressure (BP) dependent. Intrinsic heart rate (HR) dependency of cfPWV is unknown because increasing HR is commonly accompanied by increasing BP. This study aims to quantify cfPWV dependency on acute, sympathovagal-independent changes in HR, independent of BP. Individuals (n=52, age 40–93 years, 11 female) with in situ cardiac pacemakers or cardioverter defibrillators were paced at 60, 70, 80, 90, and 100 bpm. BP and cfPWV were measured at each HR. Both cfPWV (mean [95% CI], 0.31 [0.26–0.37] m/s per 10 bpm; P <0.001) and central aortic diastolic pressure (3.78 [3.40–4.17] mm Hg/10 bpm; P <0.001) increased with HR. The HR effect on cfPWV was isolated by correcting the BP effects by 3 different methods: (1) statistically, by a linear mixed model; (2) mathematically, using an exponential relationship between BP and cross-sectional lumen area; and (3) using measured BP dependency of cfPWV derived from changes in BP induced by orthostatic changes (seated and supine) in a subset of subjects (n=17). The BP-independent effects of HR on cfPWV were quantified as 0.20 [0.11–0.28] m/s per 10 bpm ( P <0.001, method 1), 0.16 [0.11–0.22] m/s per 10 bpm ( P <0.001, method 2), and 0.16 [0.11–0.21] m/s per 10 bpm ( P <0.001, method 3). With a mean HR dependency in the range of 0.16 to 0.20 m/s per 10 bpm, cfPWV may be considered to have minimal physiologically relevant changes for small changes in HR, but larger differences in HR must be considered as contributing to significant differences in cfPWV. Abstract : Supplemental Digital Content is available in the text.